The Teacher Development Process in Authentic Assessment of School under the Provincial Administrative Organization - Nusen, Natchanan; Semakhun, Chumpol; Comesorn, Sukkaew (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2018)
The research in teacher development process in authentic assessment of school under the Provincial Administrative Organization aimed to develop, test, and evaluate the quality of the teacher development process in learning measurement and evaluation according to the authentic conditions of school under the Provincial Administrative Organization. The samples were 28 teachers of Sri Intaratit Pittayakom School under Phitsanulok Provincial Administrative Organization. The research instruments were Need Assessment questionnaire, the evaluation form of performance, the evaluation form of quality of teacher development process. The statistics used for data analysis were percentage, mean ( ), standard deviation (S.D.), paired samples t-test, Modified Priority Need Index for Priority (PNI) as well as content analysis for qualitative data. The research results found that: The teacher development process in authentic assessment of school under the Provincial Administrative Organization by using APPA consisted of 4 steps as follows: Step 1 Need Analysis (A), Step 2. Developmental Plan (P), Step 3. Teacher development process (P), Step 4. Assessment (A). The testing and quality evaluation of teacher development process in learning measurement and evaluation according to authentic assessment of school under the Provincial Administrative Organization, the ability on evaluation of teachers who had entered this development process showed the “Passed” level of criteria in quality evaluation of teacher development process. In terms of usefulness, possibility, and propriety, overall they were at a high level.